Benthic diatoms and phytoplankton diversity in urban streams and ponds: charting a course for conservation - A. T. Castro-Castellon; M. J. Hill; E. Conroy; A. Daw; H. Gurung; J. S. Hernández-Avilés; S. J. Hobbs; V. H. Salinas-Camarillo; I. Thornhill (Biodiversity and Conservation, 2026)
Benthic diatom and phytoplankton communities are key indicators of freshwater ecosystem health and change but remain understudied. A better understanding of their distribution and abundance drivers is crucial for effective biodiversity assessment and conservation. This study adopts a novel, multi-ecosystem approach to examine the seasonal (2019–2020) diversity of benthic diatom assemblages in urban streams and phytoplankton assemblages in ponds across Bristol (UK) and the local environmental factors shaping these communities. Among ponds, winter recorded significantly fewer phytoplankton taxa than summer and autumn. Among streams, patterns of benthic diatom beta diversity indicated higher turnover in autumn than in winter, and among pond habitats, turnover dominated in the summer and autumn seasons, but nestedness explained more of the composition variation in winter. No significant differences in Local Contributions to Beta Diversity (LCBD) were recorded between seasons for either streams or ponds. However, among streams, LCBD was consistently high at sites with elevated phosphorus, indicating how nutrient enrichment can shape unique assemblages. In streams, nitrate emerged as the principal driver of diatom diversity and composition during the autumn season, whilst, pH, ammonium, zinc, and potassium distinguished diatom communities during the winter. In ponds, pH influenced phytoplankton assemblages in summer, possibly through nutrient and inorganic carbon availability changes. However, no strong environmental–species relationships were identified in autumn or winter, suggesting biotic interactions may be more influential during these seasons. We highlight the need for more comprehensive, long-term monitoring for the inclusion of diatoms and phytoplankton in urban freshwater management and conservation strategies.